A data-driven goal programming model for the nurse scheduling problem. (1st January 2013) - Abdollahi, Sayehed Maryam; Ansari, Zahra
The nurse scheduling problem is one of the most important challenges for human resources managers in the healthcare field. The problem deals with shift arrangements for the nursing staff. Real-world nurse scheduling schemes are often faced with various regulations related to safety and quality of services. In this paper, a goal programming-based nurse scheduling model is developed. The proposed model accounts for management policies and nurses' non-uniform work schedules by incorporating their scheduling preferences. Data were collected from the intensive care unit (ICU) ward of Isfahan Dr. Shariati hospital located in Iran and analysed as a case study. In an attempt to meet nurses' scheduling preferences and priorities, their importance weights were calculated using the analytical hierarchy process technique based on the criteria that were identified by the head nurse. The proposed model was solved by LINGO, an optimisation software package. Results were analysed and findings were summarised.